Combination of gefitinib and olaparib versus gefitinib alone in EGFR mutant non-small-cell lung cancer (NSCLC): A multicenter, randomized phase II study (GOAL). (December 2020) - Garcia-Campelo, Rosario; Arrieta, Oscar; Massuti, Bartomeu; Rodriguez-Abreu, Delvys; Granados, Ana Laura Ortega; Majem, Margarita; Vicente, David; Lianes, Pilar; Bosch-Barrera, Joaquim; Insa, Amelia; Dómine, Manuel; Reguart, Noemí; et al.
Highlights: A phase II randomized study of gefitinib versus gefitinib plus olaparib in 182 EGFR-mutation positive NSCLC patients. The study included patients from Spain and Mexico. Median progression-free survival was 10.9 months in the gefitinib compared to 12.8 months in the gefitinib plus olaparib arm. Abstract: Objectives: Progression-free survival (PFS) and response rate to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) varies in patients with non-small-cell lung cancer (NSCLC) driven by EGFR mutations, suggesting that other genetic alterations may influence oncogene addiction. Low BRCA1 mRNA levels correlate with longer PFS in erlotinib-treated EGFR -mutant NSCLC patients. Since the poly (ADP-ribose) polymerase (PARP) inhibitor, olaparib, may attenuate and/or prevent BRCA1 expression, the addition of olaparib to gefitinib could improve outcome in EGFR -mutant advanced NSCLC. Materials and methods: GOAL was a multicenter, randomized phase IB/II study performed in two countries, Spain and Mexico. Eligible patients were 18 years or older, treatment-naïve, pathologically confirmed stage IV NSCLC, with centrally confirmed EGFR mutations and measurable disease. Patients were randomly allocated (1:1) to receive gefitinib 250 mg daily or gefitinib 250 mg daily plus olaparib 200 mg three times daily in 28-day cycles. The primary endpoint was PFS. Secondary endpoints included overall survival (OS), response rate, safety and tolerability. Results: Between September 2013, and July 2016, 182 patients underwent randomization, 91 received gefitinib and 91 received gefitinib plus olaparib. There were no differences in gender, age, smoking status, performance status, presence of bone and brain metastases or type of EGFR mutation. Median PFS was 10.9 months (95 % CI 9.3–13.3) in the gefitinib arm and 12.8 months (95 % CI 9.1–14.7) in the gefitinib plus olaparib arm (HR 1.38, 95 % CI 1.00–1.92; p = 0.124). The most common adverse events were anemia, 78 % in gefitinib plus olaparib group, 38 % in gefitinib arm, diarrhea, 65 % and 60 %, and fatigue, 40 % and 32 %, respectively. Conclusions: The gefitinib plus olaparib combination did not provide significant benefit over gefitinib alone. The combination's safety profile showed an increase in hematological and gastrointestinal toxicity, compared to gefitinib alone, however, no relevant adverse events were noted.